2023
DOI: 10.3390/w15061124
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Water-Nitrogen Regulation Mode to Improve Productivity of Mixed-Sowing Grassland of Bromus inermis and Alfalfa

Abstract: Scientific selection of appropriate herbage planting management mode is an important guarantee to promote artificial grassland development and grassland productivity. In this study, three-year-old alfalfa (Medicago sativa L.) and bromus inermis were applied to analyze the effects of planting patterns (bromus inermis and alfalfa mixed-sowing D1, bromus inermis mono-sowing D2), nitrogen application (pure nitrogen) level (N1: 60 kg·ha−1, N2: 120 kg·ha−1), and water regulation (upper and lower limits of irrigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In addition, it was found that PEPN was significantly affected by irrigation and N application, and fertilization had a greater effect on NUE than irrigation. This further suggests that optimizing water and N supply can improve alfalfa N use efficiency, thereby increasing productivity ( Kang et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that PEPN was significantly affected by irrigation and N application, and fertilization had a greater effect on NUE than irrigation. This further suggests that optimizing water and N supply can improve alfalfa N use efficiency, thereby increasing productivity ( Kang et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dried samples were pulverized and passed through a 40-mesh screen for subsequent measurements. The crude protein (CP) content was determined using the Kjeldahl method (Kang et al, 2023). The crude fat (EE) content was determined using the Soxhlet extraction method (Sosnowski and Truba, 2023).…”
Section: Analysis Of Chemical Composition and Fermentation Qualitymentioning
confidence: 99%
“…The crude ash (Ash) content was determined using the high-temperature burning method in a muffle furnace (Sosnowski and Truba, 2023). The relative feeding value (RFV) was calculated according to the method described by Kang et al (2023). The samples (20 g) were mixed and homogenized with sterile water (180 mL) and filtered through four layers of gauze for the determination of fermentation indicators.…”
Section: Analysis Of Chemical Composition and Fermentation Qualitymentioning
confidence: 99%